2014
DOI: 10.5430/ijhe.v3n2p120
|View full text |Cite
|
Sign up to set email alerts
|

The Academic Achievement of Elite Athletes at an Australian University: Debunking the Dumb Jock Syndrome

Abstract: Elite athletes and their academic achievement in higher education have long been subject to considerable debate within North American scholarship. This interest proliferated especially after the release of the Knight Report (2001), which, amongst other findings, revealed a clear negative link between elite athletes and their academic achievement. While sport has always had a long and prominent presence in Australian higher education, both sport and education scholars have given very little attention to this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…12 In contrast, research on Australian elite athletes suggests that University students in elite sports perform similarly or better than their peers across various educational markers. 26 Considering elite sports literature regarding life skills, some evidence suggests higher autonomy in elite compared with community soccer players, 11 while qualitative research on Indian female cricketers suggests that elite athletes report low environmental mastery, low personal growth and low autonomy. 27 Similarly, although life skill development opportunities are offered in many Australian sporting systems, one study in Australian Rules Football reported failing to connect skills learnt in these programmes to life after sport.…”
Section: Physical Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In contrast, research on Australian elite athletes suggests that University students in elite sports perform similarly or better than their peers across various educational markers. 26 Considering elite sports literature regarding life skills, some evidence suggests higher autonomy in elite compared with community soccer players, 11 while qualitative research on Indian female cricketers suggests that elite athletes report low environmental mastery, low personal growth and low autonomy. 27 Similarly, although life skill development opportunities are offered in many Australian sporting systems, one study in Australian Rules Football reported failing to connect skills learnt in these programmes to life after sport.…”
Section: Physical Healthmentioning
confidence: 99%
“…Existing findings are mixed regarding these relationships. While some research indicates that talent development athletes may be at risk of sacrificing educational and occupational endeavours 12 13 , isolation from non-sporting social supports 25 and impacted life skills (eg, low environmental mastery 27 ), other findings suggest high-performance athletes achieve similar educational outcomes to their peers 26 and develop a range of transferable skills through talent development sports involvement 29 . One explanation for the healthier developmental markers found in the current study's talent development sample may be that AFL talent pathways facilitate the management of sport and life commitments to limit the impacts of sport on external life domains and encourage educational completion, for example, by preventing players from being approached by clubs during school exam periods.…”
Section: Equity Diversity and Inclusion Statementmentioning
confidence: 99%